PERANCANGAN JARINGAN INTERNET BERBASIS MIKROTIK ROUTERBOARD UNTUK MANAJEMENBANDWIDTH - ., Muliadi (Faculty of Engineering, Universitas Tanjungpura, 2018)
Communication without wires / wireless (wireless) has become the basic needs or new lifestyle of society, especially in the field of information. Wireless LANs are better known as Wifi networks to be an alternative technology and relatively easier to implement in familiar working environments such as schools, colleges, offices, cafes and companies and other agencies. Installation of Wifi network devices is more flexible because it does not require a cable connector between computers. Access point is a device commonly used in wireless networks where users or users connect to the internet using the air media through the access point device. In addition, with wireless-based network that makes the community especially RT / RW easier to access the internet, Implementation of this network installation consists of installation of RJ-45 connectors on UTP cable, repeater configuration, Access Point configuration, HotSpot Server configuration and others .Â Keywords: Wireless, MikroTik, HotSpot, and Access Point.Â